The Implementation of the Islamic Singing Method to Instill a Love for Islam in Early Childhood Children at TK IT Al-Fikri, Koto Raja - Dewi Lestari; Nikmatur rohmah; Nurlismi; Mukhlas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Early Childhood Islamic Education (PIAUD) plays a crucial role in shaping children's character from an early age. One of the methods that can be applied in Islamic learning is the Islamic singing method. This method utilizes songs with lyrics containing Islamic teachings, such as tauhid, noble morals, and daily prayers. This study aims to analyze the effectiveness of the Islamic singing method in instilling a love for Islam in early childhood at TK IT Al-Fikri, Koto RajaThis research employs a qualitative approach with a descriptive method. Data were collected through observations, interviews with teachers and parents, and documentation of learning activities. The findings indicate that the Islamic singing method helps children easily understand Islamic concepts and increases their interest in religious learning. Additionally, this method creates an enjoyable learning atmosphere, enhances children's memory, and strengthens their Islamic character. In conclusion, the Islamic singing method is an effective learning strategy for instilling Islamic values in early childhood. Proper implementation can foster children's love for Islam and help them grow into individuals with noble character in accordance with Islamic teachings.